Some aspects of in vitro studies of neurotoxicity: from choice of biochemical and molecular markers to the confirmation of their informativity - Chekman, I. S.; Trachtenberg, I. М.; Belenichev, I. F.; Buhtiyarova, N. V.; Gorchakova, N. A.; Levich, S. V.; Бєленічев, Ігор Федорович; Бухтіярова, Ніна Вікторівна; Левіч, Сергій Вадимович (Bulgaria: Hikari Ltd, 2017)
The use of laboratory animals in pharmacological and toxicological studies is axiomatic from the point of experimental science and will always be conducted. But these studies are laborious, require additional personnel, the presence of a vivarium, cause the suffering of animals and their death. Therefore, since the late 80's of the last century in the scientific community of Europe and the US actively discusses the issue of toxicological studies in vitro and, in particular, neurotoxicological studies in vitro. But the use of various molecular and biochemical markers of the central nervous system in neurotoxicological studies in vitro, as well as the morphometric parameters of a neuron, can be difficult, because they can be changed by neuroprotective, and not neurotoxic, action of a potential drug. That's why, it is necessary to identify and use molecular or biochemical markers, that make it possible to clearly judge about only the neurotoxicity of the drugs.
Keywords: neurotoxicity; in vitro studies; markers; reduced glutathione; nitrotyrosine